Core cross-linked micelles of polyphosphoester containing amphiphilic block copolymers as drug nanocarriers. Issue 48 (27th April 2016) - Yilmaz, Z. Ergul; Vanslambrouck, S.; Cajot, S.; Thiry, J.; Debuigne, A.; Lecomte, P.; Jérôme, C.; Riva, R.
Abstract : Poly(ethylene oxide)- b -polyphosphoester bearing unsaturations are promising materials for drug delivery applications. Abstract : Poly(ethylene oxide)- b -polyphosphoester amphiphilic block copolymers are known to self-assemble into polymer micelles when dissolved in water. This work aims at reporting on the improvement of the stability of the micelles at high dilution by crosslinking the hydrophobic polyphosphoester micellar core. Typically, an unsaturated alkene side-chain was introduced onto the cyclic phosphate monomer according to a one-step reaction followed by its organocatalyzed polymerization initiated by a poly(ethylene oxide) macroinitiator. This strategy avoids the use of any organometallic compounds in order to facilitate the purification and meet the stringent requirements of biomedical applications. After self-assembly in water, the micelles were cross-linked by simple UV irradiation. These cross-linked micelles have then been loaded with doxorubicin to evaluate their potential as drug nanocarriers and monitor the impact of crosslinking on the release profile.